Mobile money services widen financial inclusion and the development of its ecosystem : a report on Robi Axiata Limited - Chowdhury, Sifat Tasnim (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.